1999
DOI: 10.1109/70.817668
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly and self-repair method for a distributed mechanical system

Abstract: Abstract-We propose a self-assembly and self-repair method for a homogeneous distributed mechanical system. We focus on a category of distributed systems composed of numbers of identical units which can dynamically change connections among themselves. Each unit has an on-board microprocessor, and local communication between neighboring units is possible. In this paper, we discuss a distributed method for a group of such units to metamorphose from an arbitrary configuration into a desired configuration through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(58 citation statements)
references
References 10 publications
0
57
0
1
Order By: Relevance
“…Murata et al originally developed the Fracta robot system [8] [9], which can reconfigure by rotating units about each other. Tomita et al [10] have since extended this work to a system in which modules can climb over one another, and Yoshida et al [11] have developed a miniaturized selfreconfigurable robot. Ichikawa et al [12] have demonstrated a collective robotics system in which individual robots can attach and detach from each other to form variable multirobot structures.…”
Section: Introductionmentioning
confidence: 99%
“…Murata et al originally developed the Fracta robot system [8] [9], which can reconfigure by rotating units about each other. Tomita et al [10] have since extended this work to a system in which modules can climb over one another, and Yoshida et al [11] have developed a miniaturized selfreconfigurable robot. Ichikawa et al [12] have demonstrated a collective robotics system in which individual robots can attach and detach from each other to form variable multirobot structures.…”
Section: Introductionmentioning
confidence: 99%
“…Another application is space/planetary exploration, where unpredictable terrains on a planet have to be explored by a robot before human beings are sent (Jantapremjit and Austin, 2001). In the literature, it is possible to find several modular designs (Murata et al, 1998, Kotay et al, 1999, Casal and Yim 1999, Fukuda and Nakagawa 1988, Yim et al, 2000, Castaño and Will, 2000, Pamecha et al, 1996, Fukuda and Kawauchi , 1990, Suh et al, 2002, Tomita et al, 1999, Ünsal and Khosla 2000 where authors developed the hardware and the control software. Development of functional selfreconfigurable robots is a significant challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Lattice robots like MAAM (Gueganno and Duhaut, 2004), Crystalline (Vona and Rus, 2000), Telecube (Vassilvitskii et al, 2002), Fractum (Tomita et al, 1999), ATRON (Østergaard and Lund, 2003) and I-Cubes (Unsal et al, 2000) locomote by moving modules to neighbouring positions on a lattice. Chain robots like M-TRAN (Kurokawa et al, 2003), Polybot , Conro (Castano et al, 2002) and Y1 (Gonzalez-Gomez and Boemo, 2005) (González-Gó mez et al, 2004) for an example of a robot using a single FPGA for controlling all modules and (Gueganno and Duhaut, 2004) for a modular robot using an FPGA for each module.…”
Section: Introductionmentioning
confidence: 99%